PENGARUH EFIKASI DIRI, LINGKUNGAN KELUARGA, DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA SMK DI SIDOARJO - Maftuhah, Rifaatul; Suratman, Bambang (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
This study aimed to analyze the influence of self-efficacy, family environment, and entrepreneurial knowledge towards the entrepreneurial interest of vocational school students in Sidoarjo. The population in this study are class XI student of SMK in Sidoarjo, Business and Management group 2014-2015. The sampling technique using proportional sampling technique. The sample consisted of 250 students. Methods of analysis using multiple linear regression. Results of the data shows that self-efficacy has partial positive significant effect on the interest in entrepreneurship of vocational school students in Sidoarjo. While the family environment has partial positive significant effect on entrepreneurial interest for vocational school students in Sidoarjo. Then entrepreneurial knowledge has partially positive significant effect on the interest in entrepreneurship vocational school students in Sidoarjo. Results of the data analysis shows that simultaneously self-efficacy, entrepreneurial knowledge, and family environment have a positive significant effect on the interest in entrepreneurship of vocational school students in Sidoarjo